Liver lesions Ohrid minnow moranec (Pachychilon pictus Heck. et Kner) collected from some contaminated sites of Lake Ohrid - Roganović-Zafirova, Danica; Tavciovska-Vasileva, Irena (Macedonian Journal of Ecology and Environment, 1999)
Histopathological findings in the liver of Ohrid minnow collected from polluted areas were presented in this study. Extensive inflammatory lesions surrounding blood vessels and bile ducts accompanied by necrotic areas and occasional parasitic infestation were recognized as a consistent observation. Particular attention was paid to bile duct proliferation as a possible pollution-induced lesion.